1998
DOI: 10.1159/000020812
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Septostomy for the Treatment of Twin Oligohydramnios-Polyhydramnios Sequence

Abstract: Objective: To report our experience with intentional puncture of the intervening membrane (‘septostomy’) for the treatment of the twin oligohydramnios-polyhydramnios sequence (TOPS). Methods: 12 patients were diagnosed with TOPS based on ultrasonographic findings. A 20- to 22-gauge spinal needle was used to puncture the membrane between the twins without any attempt at amnioreduction in 9 patients, while the procedure was combined with amnioreductions in 3 patients. Results: Gestational age was 23.1 ± 3.3 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 28 publications
3
61
1
4
Order By: Relevance
“…The survival with AR is significantly better in the NIH trial (60%) than in the Eurofoetus trial (41%) and consistent with single institution series [6][7][8][9][10][11][12] , a prospective randomized trial 15,16 , and registries (60-65%) 34,35 . This may be due to the standardized aggressive protocol used for serial AR in the NIH trial.…”
Section: Commentssupporting
confidence: 70%
See 2 more Smart Citations
“…The survival with AR is significantly better in the NIH trial (60%) than in the Eurofoetus trial (41%) and consistent with single institution series [6][7][8][9][10][11][12] , a prospective randomized trial 15,16 , and registries (60-65%) 34,35 . This may be due to the standardized aggressive protocol used for serial AR in the NIH trial.…”
Section: Commentssupporting
confidence: 70%
“…This inadvertent septostomy has been suggested to account for the "single amnioreduction paradox" in which TTTS appears to stop in up to 20% of patients after only a single AR 36 . Consistent with this view, a prospective randomized trial comparing AR to septostomy found the same 65% survival in each arm of the study 16 . The problem with septostomy has been the risk of creating a mono-amniotic gestation and the attendant risk of cord entanglement with double fetal demise 37 .…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Septostomy using the intentional perforation of the interamniotic membrane to equalize the volume of amniotic fluid in cases of severe TTTS was first introduced by Saade et al 8 Septostomy interrupts the polyhydramnios-oligohydramnios mechanism and induces an amniotic fluid volume increase in the gestational sac of the 'donor' twin, which has been associated with an increase in the circulatory volume, as well as renal perfusion and urinary output. Similarly, septostomy also may benefit the 'recipient' fetus, because when the volume of amniotic fluid and hydrostatic pressure between the gestational sacs are normalized, the inflow of water from the maternal compartment is prevented.…”
Section: Discussionmentioning
confidence: 99%
“…7 Septostomy, a rupture of the diamniotic membrane separating monozygotic twins essentially creating a monoamniotic gestation, has also been reported as a potential therapeutic modality for TTTS. 3,8 Some complications of septostomy have been reported, including cord entanglement and complete rupture of membranes of both twins, but amniotic band syndrome (ABS) associated with septostomy has never been reported. We report a case of severe ABS with limb amputation after septostomy.…”
Section: Introductionmentioning
confidence: 99%